A Refined Single-Particle Reconstruction Procedure to Process Two-Dimensional Crystal Images from Transmission Electron Microscopy. (20th May 2015) - Kuang, Qie; Purhonen, Pasi; Pattipaka, Thirupathi; Ayele, Yohannes H.; Hebert, Hans; Koeck, Philip J.B.
Abstract: Single-particle reconstruction (SPR) and electron crystallography (EC), two major applications in electron microscopy, can be used to determine the structure of membrane proteins. The three-dimensional (3D) map is obtained from separated particles in conventional SPR, but from periodic unit cells in EC. Here, we report a refined SPR procedure for processing 2D crystal images. The method is applied to 2D crystals of melibiose permease, a secondary transporter in Escherichia coli . The current procedure is improved from our previously published one in several aspects. The "gold standard Fourier shell correlation" resolution of our final reconstruction reaches 13 Å, which is significantly better than the previously obtained 17 Å resolution. The choices of different refinement parameters for reconstruction are discussed. Our refined SPR procedure could be applied to determine the structure of other membrane proteins in small or locally distorted 2D crystals, which are not ideal for EC.